The feasibility of triggers for the integration of Standardised, Early Palliative (STEP) Care in advanced cancer: A phase II trial - Collins, Anna; Sundararajan, Vijaya; Le, Brian; Mileshkin, Linda; Hanson, Susan; Emery, Jon; Philip, Jennifer (Frontiers in Oncology, 2022)
Background: While multiple clinical trials have demonstrated benefits of early palliative care for people with cancer, access to these services is frequently very late if at all. Establishing evidence-based, disease-specific ‘triggers’ or times for the routine integration of early palliative care may address this evidence-practice gap. Aim: To test the feasibility of using defined triggers for the integration of standardised, early palliative (STEP) care across three advanced cancers. Method: Phase II, multi-site, open-label, parallel-arm, randomised trial of usual best practice cancer care +/- STEP Care conducted in four metropolitan tertiary cancer services in Melbourne, Australia in patients with advanced breast, prostate and brain cancer. The primary outcome was the feasibility of using triggers for times of integration of STEP Care, defined as enrolment of at least 30 patients per cancer in 24 months. Triggers were based on hospital admission with metastatic disease (for breast and prostate cancer), or development of disease recurrence (for brain tumour cohort). A mixed method study design was employed to understand issues of feasibility and acceptability underpinning trigger points. Results: The triggers underpinning times for the integration of STEP care were shown to be feasible for brain but not breast or prostate cancers, with enrolment of 49, 6 and 10 patients across the three disease groups respectively. The varied feasibility across these cancer groups suggested some important characteristics of triggers which may aid their utility in future work. Conclusions: Achieving the implementation of early palliative care as a standardized component of quality care for all oncology patients will require further attention to defining triggers. Triggers which are 1) linked to objective points within the illness course (not dependent on recognition by individual clinicians), 2) Identifiable and visible (heralded through established service-level activities) and 3) Not reliant upon additional screening measures may enhance their feasibility.